Accuracy of movement quality screening to document effects of neuromuscular control retraining exercises in a young ex-footballer with hip and groin symptoms: A proof of concept case study. (November 2018) - Wilson, David A.; Booysen, Nadine; Dainese, Paolo; Heller, Markus O.; Stokes, Maria; Warner, Martin B.
Abstract: Hip and groin pain is common in footballers and altering movement patterns can reduce symptoms. Observational tests of movement control are thought to identify abnormal movement patterns, but their accuracy needs yet to be confirmed by comparison with an objective measure. To assess the accuracy, using 3D motion analysis, of observational movement control tests and their ability to detect changes, and document changes in symptoms following a neuromuscular control exercise programme in an ex-footballer with hip and groin pain. A 25-year-old male with chronic bilateral hip and groin pain had their movement control ability rated and kinematic data collected using 3D motion analysis while performing Small Knee Bend (SKB) and SKB with Rotation (SKB Rot) tests pre-and post-neuromuscular control exercise training. Movement control was rated as at fault if they were unable to control specific trunk and pelvic movements during the tests. The Copenhagen Hip and Groin Outcome Score (HAGOS) was used to assess symptoms. Following the intervention, observational rating during the SKB test improved from fault to no fault for anterior pelvic tilt, which decreased by 17° and 16° during right and left leg SKB tests respectively. The HAGOS symptoms subsection improved from 36% to 61%. Observational movement screening ratings were supported by 3-D motion analysis. These findings indicate that the screening tool was accurate for detecting improvements in trunk and pelvic movement control following an exercise programme in an ex-footballer who had presented with hip and groin pain.